2017
DOI: 10.1002/term.2474
|View full text |Cite
|
Sign up to set email alerts
|

Needleless emulsion electrospinning for the regulated delivery of susceptible proteins

Abstract: In the present work, we developed a novel needleless emulsion electrospinning technique that improves the production rate of the core/shell production process. The nanofibres are based on poly-ε-caprolactone (PCL) as a continuous phase combined with a droplet phase based on Pluronic F-68 (PF-68). The PCL-PF-68 nanofibres show a time-regulated release of active molecules. Needleless emulsion electrospinning was used to encapsulate a diverse set of compounds to the core phase [i.e. 5-(4,6-dichlorotriazinyl) amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The emulsion electrospinning results in the formation of bres for long-term delivery of active molecules. 38 In the case of centrifugal spinning, 19 the bres showed a similar release pattern and the mean release time was shorter than in the studies with electrospun bres. [39][40][41] Nevertheless, the amount of the total protein released (Fig.…”
Section: Release Of Platelet Lyophilisate From the Core-shell Brous Scaffoldsmentioning
confidence: 80%
“…The emulsion electrospinning results in the formation of bres for long-term delivery of active molecules. 38 In the case of centrifugal spinning, 19 the bres showed a similar release pattern and the mean release time was shorter than in the studies with electrospun bres. [39][40][41] Nevertheless, the amount of the total protein released (Fig.…”
Section: Release Of Platelet Lyophilisate From the Core-shell Brous Scaffoldsmentioning
confidence: 80%
“…Organic solvents may negatively influence bioactivity of bioactive substances; therefore, core-shell electrospinning where hydrophilic polymers such as PVA is in the core is preferred [ 168 , 169 ]. However, other methods, e.g., needleless electrospinning, can also lead to the production of core-shell nanofibers when using an emulsion system for the preparation of nanofibers [ 169 , 170 , 171 ]. On the other hand, water soluble polymers, e.g., PVA, PEO, PEG, gelatine, hyaluronic acid, and collagen are often used as blends or in composite scaffolds [ 172 , 173 , 174 , 175 ].…”
Section: Potential Applications Of Hybrid Multifunctional Nanofibersmentioning
confidence: 99%
“…The aim of the system is to provide dual delivery of GFs, and this was achieved by encapsulating nerve growth factor (NGF) and glial cell line-derived neurotrophic factor (GDNF) individually in poly(d,l-lactic acid) (PDLLA) and PLGA fibers, respectively by emulsion electrospinning. A current study of needleless emulsion electrospinning also has been reported, which aims to overcome low productivity of conventional emulsion electrospinning [122]. Horseradish peroxidise (HRP) and multiple GFs (transforming growth factor-β (TGF-β), basic fibroblast growth factor (bFGF), and insulin growth factor-1 (IGF-1)) have been successfully incorporated in the core layer of this system.…”
Section: Emulsion Electrospinningmentioning
confidence: 99%
“…Horseradish peroxidise (HRP) and multiple GFs (transforming growth factor-β (TGF-β), basic fibroblast growth factor (bFGF), and insulin growth factor-1 (IGF-1)) have been successfully incorporated in the core layer of this system. In vitro testing revealed that the as-prepared core-shell fibers promote viability and metabolic activity of porcine mesenchymal stem cells (MSCs) [122].…”
Section: Emulsion Electrospinningmentioning
confidence: 99%